Etymology of American reptile genera - Uetz, Peter H.; Lavilla, Esteban O. (Herpetologia Brasileira, 2026)
Here we provide the etymologies of all 416 extant reptile genera that occur on the American supercontinent, ranging from Canada to Argentina and Chile, but excluding the Caribbean. The 416 genera make up one third of all 1,250 reptile genera worldwide. Most of these names are still based on Greek and Latin terms (316 and 79, respectively), and about 20 names each are based on local terms, eponyms, and actual localities. The origin of some names remains mysterious (e.g. Farancia, Ficimia, Ninia), although we do offer speculations about them. More than half of all American reptile genera were coined by just 10 individuals, two of whom are still alive. The vast majority of names were coined in an intense period of discovery from around 1820 to 1880 (when many authors did not explain the origin of their names). However, a significant increase of new genus descriptions has begun in the 21st century with the advent of molecular taxonomy.